Comorbidity associated with worse outcomes in a population of limited cochlear implant performers. Issue 1 (16th December 2022) - Lee, Erika; Pisa, Justyn; Hochman, Jordan
Abstract: Introduction: Most patients significantly benefit from cochlear implantation (CI). However, speech understanding varies widely, with a small proportion of patients demonstrating limited audiometric outcomes. While there are well‐documented determinants of poor performance, there remains a cohort of patients that do not meet expected outcomes. Preoperative prognostication is desirable to manage expectations, ensure value of the intervention, and reduce risk. The objective of the study is to evaluate variables found within a single CI center's most limited functioning cohort following implantation. Methods: A retrospective review of a single CI program's cohort of (344 ears) patients implanted between 2011 and 2018 whose 1‐year postimplantation AzBio scores fall 2 SDs below the mean was performed. Exclusion criteria includes skullbase pathology, pre/peri‐lingual deafness, cochlear anatomic abnormalities, English as an additional language, and limited electrode insertion depth. Overall, 26 patients were identified. Results: The study population's postimplantation net benefit AzBio score is 18% compared to the entire program's 47% ( p  < 0.05). This group is older (71.8 vs. 59.0 years, p  < 0.05) with a longer duration of hearing loss (26.4 vs. 18.0 years, p  < 0.05) and with a lower preoperative AzBio score [14% lower ( p  < 0.05)]. A host of medical conditions were identified in the subpopulation, with a trend towards significance in those suffering from either malignancy or cardiac condition. Escalating comorbid status was associated with worse performance ( p  < 0.05). Conclusion: Within a cohort of limited‐performing CI users, benefit tended to decrease with escalating number of comorbid conditions. This information may serve to inform preoperative patient counseling. Level of evidence: Level IV (evidence from a case control study). Abstract : Many patients receive benefit from cochlear implant surgery, however a cohort of patients remain that do not perform as expected with age and duration of hearing loss the primary risk factors.